Perceptions of relative deprivation and women’s empowerment - Kosec, Katrina; Mo, Cecilia Hyunjung; Schmidt, Emily; Song, Jie (Elsevier, 2021)
How do perceptions of one’s relative economic status affect gender attitudes, including support for women’s economic participation and involvement in decision-making in their community and household? We conducted a 2018 survey experiment with female and male adults in approximately 1000 households in Papua New Guinea. Employing an established survey treatment to subtly alter respondents’ perception of their relative economic wellbeing, we find that increased feelings of relative deprivation make both men and women significantly more likely to support girls’ schooling and women’s paid employment, suggesting that relative economic insecurity can actually prompt support for women’s economic participation. However, increased feelings of relative deprivation may trigger greater intra-household tension. While increased perceptions of relative deprivation cause women to want more household decision-making authority, men’s attitudes toward women’s proper roles in decision-making are unchanged. In other words, increased support for women’s economic participation among men appears to stem mainly from a desire to raise household income, and not to alter the general role of women in society. The results underscore the multifaceted nature of gender attitudes, and how support for women’s economic participation may rise without simultaneous increases in women’s agency in decision-making.